Correction: A comprehensive mapping of stress system interactions with pain and their contribution to chronification of musculoskeletal pain: Protocol of the STRAIN study - Moerkerke, Matthijs; Vyverman, Joren; De Baere, Robrecht; Clement, Patricia; Smeets, Tom; Coppieters, Iris; Timmers, Inge; Van Oosterwijck, Jessica (PloS one, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0324089.].